Evaluation of productive and reproductive performances of local and crossbred cows in Manikgonj district of Bangladesh - Rahman, Md Habibur; Ali, Md Younus; Juyena, Nasrin Sultana; Bari, Farida Yeasmin (Asian Journal of Medical and Biological Research, 2017)
A total of 90 lactating cows from twelve dairy farms were used to conduct this study in order to evaluate the productive and reproductive performance of crossbred and local cows at farmer’s level in Manikgong district. All cows were divided into three groups, according to their genetic composition as Local, Local x Friesian and Local x Friesian x Friesian cows. The results showed late sexual maturity (37.41±0.03 months), calving interval (481.86±0.33 days), shortest lactation period (198.46±2.36 days) and lowest average milk production (2.25±0.04 L/day) in local cows. On the contrary, longest lactation period (266.43±1.18 days) and highest average milk production (7.45±0.11 L/day) were observed in LFF cows, whereas early sexual maturity (30.58±0.02 months) was found in Local x Friesian cows. From the above perspective it could be concluded that LFF crossbred cows may be suitable for profitable dairy farming in Bangladesh but herd life and life time productivity is one of the most influential factor for profitable dairy farming. However, further study with larger sample sizes covering more different management systems would be required to describe a better inference in this consideration. Asian J. Med. Biol. Res. September 2017, 3(3): 330-334